Increased Interleukin-4 in Farmers With Ascariasis in Rural Jember - Rahmadhan, Adiz Dwiputra; Armiyanti, Yunita; Hermansyah, Bagus; Helianti, Dina; Nurdian, Yudha (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2021)
Ascaris lumbricoides is nematode which often infest human in the world. The infestation of A. lumbricoides in the human will trigger the formation of Th2 immune responses through increased interleukin-4 released by innate immune cells. Th2 immune response generates B lymphocyte cells to produce IgE antibodies to eliminate A. lumbricoides. Therefore, IL-4 is a marker of Th2 immune response. The purpose of this study was to determine the prevalence of ascariasis and an increase of IL-4 in planters infested with A. lumbricoides as a marker of Th2 immune response. Our study was observational analytic with cross sectional design. 230 planters who were willing to be involved in the study gave stool samples for the diagnosis of ascariasis. 20 people who were positive for ascariasis and 20 people who were negative selected randomly for blood plasma samples. IL-4 levels in blood plasma were measured using ELISA. Differences in IL4 levels between positive and negative ascariasis were analyzed by the Mann Whitney statistical test with p value ≤ 0.05. The prevalence of ascariasis among planters in rural area of Jember was 16,52% which was included low prevalence. Univariate analysis showed that the mean and median levels of IL-4 ascariasis were greater than those of healthy planters. Mann Whitney test results showed that there were differences in levels of IL-4 between ascariasis and healthy planters (p≤0.05). Increased levels of IL-4 in planters with ascariasis indicate that A. lumbricoides infection triggers the formation of Th2 immune response as a mechanism for eliminating A. lumbricoides. Keywords: Interleukin-4, A. lumbricoides, Th2 immune response.